Two new species of Tigriopus Norman, 1869 from Chonburi Province, Thailand (Crustacea: Copepoda: Harpacticidae). - Chullasorn, S. P. Kangtia, S.J. Song & J.S. Khim (In: Huys, R. (ed.). Systematics and Taxonomy of Harpacticoid Copepods—A Commemorative Volume in Honour of Prof. John B.J. Wells, Zootaxa, 569 pp., 2021)
Two new species of the family Harpacticidae Dana, 1846, Tigriopus namsaiensis sp. nov. and T. wannapaensis sp. nov. were found in algal washings at Namsai and Wannapa beaches in Chonburi Province, Thailand. There are currently 14 known species in the genus, two of which, T. thailandensis Chullasorn, Ivanenko, Dahms, Kangtia & Yang, 2012 and T. sirindhornae Chullasorn, Dahms & Klangsin, 2013 were also discovered in Thailand. The genus Tigriopus Norman, 1869 has a worldwide distribution with nine species recorded from the Pacific Ocean (seven in the North Pacific and two in the South Pacific), four species from the Atlantic and adjacent seas, two species from the South Indian Ocean, and one species from Antarctica. Sexual dimorphism is expressed in the antennule, antenna, P2, P5, P6, and segmentation of the urosome. Tigriopus namsaiensis sp. nov. and T. wannapaensis sp. nov. are closely related to T. thailandensis and T. sirindhornae in sharing the following characters: fewer sensilla on the prosome; antennary exopod with one seta on exp-2; P4 exp-3 with two inner setae; female P5 baseoendopod with five setae; male P2 enp-2 with a seta fused to the segment; and male P5 exopod with five setae. Tigriopus namsaiensis sp. nov. closely resembles T. thailandensis, but the new species is characterized by four setae on the maxillulary coxa (three setae in T. thailandensis), the outermost seta on the female P6 is plumose (instead of the middle one), the lateral seta on the apical segment of the antennary exopod is discrete at the base (instead of fused to the segment), and the outermost seta of the male P5 exopod is plumose (instead of spinulose). Tigriopus wannapaensis sp. nov. is very closely related to T. sirindhornae, but the new species differs from the latter by the following characteristics: 2-segmented mandibular exopod (3-segmented in T. sirindhornae); five setae on the maxillulary coxa (instead of three); all setae on female P6 are plumose (instead of two plumose and one pinnate); the lateral seta on the apical segment of the antennary exopod is fused to the segment (instead of discrete at the base); and the outermost seta on the male P5 exopod is plumose (instead of spinulose). A dichotomous identification key to the 16 valid species of Tigriopus is provided